Evapotranspiration Estimates from the Water Balance and Equilibrium Models - Wilson, Richard Garth (My University, 1971)
This thesis examines the field performance of the water balance and equilibrium evapotranspiration models, and defines the environmental conditions for which they provided accurate estimates of water loss from a corn crop in Southern Ontario.
It is shown that the water balance model should be used only when surface runoff is measured and drainage is negligible. An error analysis indicated that soil moisture change could be estimated within 10 percent when measurements were conducted at six sites every eight days.
The equilibrium model predicted daily evapotranspiration within 6 percent when the latent heat exchange utilized between 65 and 80 percent of the available energy, indicating that the model can be applied within temperature limits of 17° and 32°C.
Keywords: evapotranspiration, water balance, equilibrium models, soil moisture, heat exchange